Implementações de algoritmos de controle e busca de máxima potência aplicados a conversão de energia fotovoltaica - Lucas Ricardo Almeida Muniz (2017)
This work objective to present the techniques for the design of a Boost converter applied to photovoltaic systems of distributed generation connected to the electric grid. This converter is used to search a maximum power of photovoltaic panels improving the system's efficiency independent of the climatic conditions variation and disturbances coming from the electric grid. In this research, simulations and analyzes of conventional maximum power search algorithms are presented. It is also proposed methods to improve the algorithms efficiency in the case of shading of photovoltaic panels. The Boost converter is used as the interface stage between the photovoltaic panels and the c.c. bus connected to the grid. In this context, system-modeling equations, passive component calculation, converter control design and simulations were developed for analysis and comparisons. Also are presented techniques to limit the generated power and to start the system smoothly in order to avoid equipment damage. The simulated results are discussed comparatively with the experimental results, demonstrating the effects of the system design, taking into account the stability performance and maximum energy production.